Punishment and political order - McBride, Keally D. (Law, meaning, and violence., 2007)
Most of us think of punishment as an ugly display of power. But punishment also tells us something about the ideals and aspirations of a people and their government. How a state punishes reveals whether or not it is confident in its own legitimacy and sovereignty. Punishment and Political Order examines the questions raised by the state's exercise of punitive power--from what it is about human psychology that desires sanction and order to how the state can administer pain while calling for justice. Keally McBride's book demonstrates punishment's place at the core of political administration and the stated ideals of the polity.